Optimizing Counterradicalism For The Young Generation In Preventing Terrorist Radicalism Through State Minded In Action - Puspitosari, Hervina; Indawati, Yana; Yulianingsih, Wiwin (International Journal of Educational Research & Social Sciences, 2022)
Deradicalization is guided by counterterrorism preventive measures as a strategic effort in neutralizing ideas that are considered radical and can be dangerous through a non-violent approach. This research was conducted with the aim of knowing radicalism in the younger generation, especially in higher education through questionnaires and interviews with related parties. Terrorism is currently a serious problem and endangers national security, so prevention efforts are needed. The target of the spread of radical terrorism that has infiltrated the university environment needs to be prevented and become a common concern, especially university leaders. The development of the radical flow of terrorism in the university environment can endanger the unity of the state because universities are a place for educational candidates for intellectuals, entrepreneurs, bureaucrats, technocrats and professionals. The aim of radicals is to bring about changes to the roots and for this they always use violent methods and oppose the existing structure of society. So that joint efforts are needed in preventing and overcoming the spread of radicalism, transformation of terrorism in universities. Efforts to prevent the various factors that cause radicalism are carried out with policies contained in universities and local governments through strengthening state minded in action among youth.